2022
DOI: 10.2174/1568026621666211201145800
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelics and Hallucinogens in Psychiatry: Finding New Pharmacological Targets

Abstract: Background: The therapeutic options for neurobehavioral disorders are still limited, and in many cases, they lack a satisfactory balance between efficacy and side effects. Objective: This work aims to review current evidence regarding the potential contribution of psychedelics and hallucinogens to the discovery of new drugs for treating different psychiatric disorders. Discussion: Ayahuasca/N,N-dimethyltryptamine (DMT), lysergic acid diethylamide (LSD), and psilocybin have evidence supporting their use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In recent years, the scientific community's interest in using psychedelics in treating mental disorders has grown, and there is now talk of a 'renaissance of psychedelic medicine' [ 75 , 76 ]. Several studies are investigating the potential role of these substances in the treatment of SUD and depression [ 77 ], in particular, ayahuasca [ 78 ], psilocybin [ 79 ], ketamine and esketamine [ 80 ]. In fact, a recent review on the use of psychedelics in treating psychiatric and addictive disorders [ 81 ] showed that in SUD subjects, the intensity of the acute psychedelic experience was the main predictor of the response to the drug.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the scientific community's interest in using psychedelics in treating mental disorders has grown, and there is now talk of a 'renaissance of psychedelic medicine' [ 75 , 76 ]. Several studies are investigating the potential role of these substances in the treatment of SUD and depression [ 77 ], in particular, ayahuasca [ 78 ], psilocybin [ 79 ], ketamine and esketamine [ 80 ]. In fact, a recent review on the use of psychedelics in treating psychiatric and addictive disorders [ 81 ] showed that in SUD subjects, the intensity of the acute psychedelic experience was the main predictor of the response to the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Several dozen academic works similarly address psilocybin mushrooms. Most of these articles address the potential therapeutic benefits of psilocybin and other psychoactive substances (Cadoch, 2021; Goldpaugh, 2021; Goldsmith, 2011; Miller, 2017; Scheidegger, 2021; Sousa et al., 2021; Vatan, 2021).…”
Section: Feral Literaturementioning
confidence: 99%
“…Interestingly, some of the substances under investigations are classified as schedule I drugs ( 2 ), what is meant to point to high potential for addiction and lack of approval for medical use. One of them are psychedelics, in which case the prohibition came in the 1960s and 1970s with the rise of the counterculture movement and the growing popularity of psychedelics.…”
Section: Introductionmentioning
confidence: 99%